Equol producers can have low leptin levels among prediabetic and diabetic females - Sakane, Naoki; Kotani, Kazuhiko; Tsuzaki, Kokoro; Takahashi, Kaoru; Usui, Takeshi; Uchiyama, Shigeto; Fujiwara, Shinji (Annales d'endocrinologie, 2014)
Soy isoflavones have received great attention for their beneficial effects on health and disease, i.e., in patients with diabetes. Equol is a biologically active isoflavone-related metabolite with interindividual differences in its production. The current study investigated the relationship between an equol-producing state and the levels of adipocytokine markers in a prediabetic and diabetic population. A total of 79 subjects (34 males/45 females) in a prediabetic or diabetic state recruited from the general population were examined regarding their ability to produce equol using urine samples. Clinical data, such as age, smoking as well as anthropometric and biochemical variables, including body mass index (BMI), lipids, insulin, glucose, hemoglobin A1c, leptin and adiponectin, were recorded. Equol producers exhibited lower leptin and leptin/BMI than non-producers among females. Simple correlation tests and stepwise multiple regression analyses revealed a significant inverse correlation between the leptin/BMI and equol-production. This relationship was not found in males. Female equol producers can have favorable metabolic traits in relation to leptin metabolism in this population. Further studies are needed to confirm these results. Les bénéfices de la consommation d’isoflavones du soja ont fait l’objet de nombreuses études chez les patients diabétiques. L’équol est un métabolite actif des isoflavones dont la sécrétion urinaire est très variable dans la population générale. Notre étude a recherché un lien entre l’excrétion urinaire d’équol et les marqueurs adipocytaires dans une population prédiabétique et diabétique. Sur les urines de 79 sujets (34 hommes et 45 femmes), présentant un pré diabète ou un diabète, la concentration d’équol a été mesurée. Les données cliniques et anthropométriques, y compris l’IMC, ont été enregistrées. Une prise de sang à jeun a permis de mesurer le bilan lipidique, l’insuline et la glycémie, l’hbA1C, la leptine et l’adiponectine. Dans le groupe de femmes étudiées, celles qui sécrètent de l’équol dans les urines, ont une leptine et un rapport leptine/IMC abaissés. Par analyse de corrélation simple ou de corrélation pas à pas, la relation inverse entre le rapport leptine/IMC et l’excrétion d’équol est significative. Cette relation n’a pas été retrouvée chez les hommes de cette étude. Chez les femmes prédiabétiques ou diabétiques, la capacité d’excréer de l’équol dans les urines est associée à un profil métabolique favorable notamment liée à la leptine ou son métabolisme. Des études complémentaires seront nécessaires pour confirmer ces résultats.